Qualitative Inquiry into Challenges Experienced by Registered General Nurses in the Emergency Department: A Study of Selected Hospitals in the Volta Region of Ghana - Confidence Alorse Atakro; Jerry Paul Ninnoni; Peter Adatara; Janet Gross; Michael Agbavor (Emergency Medicine International)
Registered General Nurses (RGNs) play crucial roles in emergency departments (EDs). EDs in Ghana are primarily staffed by RGNs who have had no additional formal education in emergency care. Additionally, basic, master’s, or doctoral level nursing education programs provide limited content on the complexities of emergency nursing. Nurses in EDs are affected by many challenges such as growing patient population, financial pressures, physical violence, verbal abuse, operational inefficiencies, overcrowding, and work overload. There is a paucity of research on challenges experienced by RGNs in EDs in the Volta Region of Ghana. In this qualitative study, twenty RGNs in EDs from three selected hospitals in the Volta Region of Ghana were interviewed. All recorded interviews were transcribed, reviewed several times by researchers and supervisors, and analyzed using content analysis. Five thematic categories were identified. These thematic categories of challenges were lack of preparation for ED role, verbal abuse from patients relatives, lack of resources in ED, stressful and time consuming nature of ED, and overcrowding in ED. Formal education of RGNs in the advanced role of emergency care, adequate supply of resources, increased hospital management support, and motivations for RGNs working in ED are necessary to improve the practice of emergency care.